STRENGTHENING ADMINISTRATIVE INSTITUTIONS OF ISLAMIC LAW IN MALAYSIA: AN OVERVIEW - Shuaib, Farid Sufian (Jurnal Syariah, 2008)
This article provides a review of institutions involved in the administration of Islamic law in Malaysia. It discusses briefly the historical background of the law in Malaysia that has close connections with the Malay Sultanates. The first institution that this article will consider is the Islamic Religious Council that is responsible for assisting the Sultan in administering Islamic law justly. The National Council of Islamic Religious Affairs, as a national body, should be fully utilised to help streamline the administration of Islamic law among the different states in Malaysia. Apart from issues regarding Mufti and fatwa the article proposes steps to strengthen the administration of justice in Syariah courts by looking at the tenure of judges, the status of prosecutors and the powers and jurisdiction of Syariah courts.